Australasian recommendations for quality assurance in kilovoltage radiation therapy from the Kilovoltage Dosimetry Working Group of the Australasian College of Physical Scientists and Engineers in Medicine - Hill, Robin; Healy, Brendan; Butler, Duncan; Odgers, David; Gill, Simran; Lye, Jessica; Gorjiara, Tina; Pope, Dane; Hill, Brendan (Australasian physical & engineering sciences in medicine, 2018)
The Australasian College of Physical Scientists and Engineers in Medicine (ACPSEM) Radiation Oncology Specialty Group (ROSG) formed a series of working groups to develop recommendations for guidance of radiation oncology medical physics practice within the Australasian setting. These recommendations provide a standard for safe work practices and quality control. It is the responsibility of the medical physicist to ensure that locally available equipment and procedures are sufficiently sensitive to establish compliance. The recommendations are endorsed by the ROSG, have been subject to independent expert reviews and have also been approved by the ACPSEM Council. For the Australian audience, these recommendations should be read in conjunction with the Tripartite Radiation Oncology Practice Standards and should be read in conjunction with relevant national, state or territory legislation which take precedence over the ACPSEM publication Radiation Oncology Reform Implementation Committee (RORIC) Quality Working Group, RANZCR, 2011a; Kron et al. Clin Oncol 27(6):325–329, 2015; Radiation Oncology Reform Implementation Committee (RORIC) Quality Working Group, RANZCR, 2018a, b).